Visual Perception of Facial Emotional Expressions during Saccades - Barabanschikov, Vladimir A. (Behav Sci (Basel), 2019)
The regularities of visual perception of both complex and ecologically valid objects during extremely short photo expositions are studied. Images of a person experiencing basic emotions were displayed for as low as 14 ms amidst a saccade spanning 10 degrees of visual angle. The observers had a main task to recognize the emotion depicted, and a secondary task to point at the perceived location of the photo on the screen. It is shown that probability of correct recognition of emotion is above chance (0.62), and that it depends on its type. False localizations of stimuli and their compression in the direction of the saccade were also observed. According to the acquired data, complex environmentally valid objects are perceived differently during saccades in comparison to isolated dots, lines or gratings. The rhythmic structure of oculomotor activity (fixation–saccade–fixation) does not violate the continuity of the visual processing. The perceptual genesis of facial expressions does not take place only during gaze fixation, but also during peak speed of rapid eye movements both at the center and in closest proximity of the visual acuity area.